High-Resolution Image Analysis Reveals a Decrease in Lens Thickness and Cone Density in a Cohort of Young Myopic Patients - Xin, Xiaoyu; Guo, Qingge; Ming, Shuai; Liu, Changgeng; Wang, Zhongfeng; Lei, Bo (Frontiers in medicine, 2021)
Purpose: To study the association between axial length (AL) and the thickness of the lens, retina, choroid, and cone density with swept-source optical coherence tomography (SS-OCT) and an adaptive optics (AO) fundus camera. Design: A prospective cross-sectional study. Methods: This study included 136 eyes in 68 subjects. SS-OCT was used to quantify the thickness of the lens, ganglion cell complex (GCC) layer, inner nuclear layer (INL), outer retinal layer (ORL), and choroid layer. Adaptive optics was used to quantify spatial features of the cone photoreceptors, including density, spacing, regularity, and dispersion. The associations among the AL and the thickness of lens, retina, choroid, and cone features were evaluated with linear regression. Results: With the severity of myopia, the increased AL was associated with thinning of the lens ( P < 0.001, 95% CI: −100.42 to −49.76). The thickness of the ORL and choroid decreased significantly (all P < 0.001), whereas the thickness of the GCC and INL decreased only in the outer ring (both P < 0.01). There was a significant correlation between the cone density/spacing and AL (both P < 0.001). Although cone density was reduced from 25,160/mm 2 to 19,134/mm 2 in the inner region and from 17,458/mm 2 to 13,896/mm 2 in the outer region, the best-corrected visual acuity (BCVA) was 20/20 or greater. Conclusions: We found that the lens thickness (LT), ORL, and cone density decreased in myopia. While decreasing cone density and ORL thickness should be related to axial elongation, decreasing of LT might imply intrinsic physical accommodation. These results provide further morphological changes of myopia.